Virtual Team Effectiveness: An Experiential Activity. (August 2013) - Gilson, Lucy L.; Maynard, M. Travis; Bergiel, Erich B.
Although the topic of virtual teams has created interest within the academic and practitioner literature, there is a lack of research on how to teach or train individuals to be effective members of such teams. To address this gap, we developed a virtual team activity that we have been using in our undergraduate business courses for 6 years. The activity is designed such that teams with members from several geographically dispersed universities work together via technology to experience the inherent differences of working within virtual teams. Here, we highlight some of the key facets of the activity as well as modifications we have made to improve the learning experience. We also discuss the debriefing sessions that are provided to classes, several pedagogical issues, and some student feedback that we have received.